Renewable energy in Central Asian economies: Role in reducing regional energy insecurity - Elena Shadrina (Asian Development Bank Institute (ADBI), 2019)
Ideally, to reduce energy insecurity, a nation needs to deploy a range of renewable energy (RE) sources. For Central Asian economies, renewable sources appear to be a rational choice; yet, the deployment of renewables is limited and varies substantially by country. Conventional statistics for RE in Central Asia confirm the expected: hydrocarbon-poor countries (Kyrgyz Republic and Tajikistan) rely on RE to a greater extent than fuel-rich economies (Kazakhstan, Turkmenistan, and Uzbekistan). However, this picture changes drastically once a stricter definition of RE - without the contribution of large-scale hydro power plants (LSHPPs) - is incorporated. Such treatment is appropriate due to several considerations, including sustainability, as the LSHPPs are infamous for their adverse environmental impacts; and security, as the water-energy nexus leaves national energy policymaking susceptible to sometimes arduous regional consensus. The latter aspect is especially relevant in the Central Asian setting. Thus, with the strict definition of RE applied, fossil fuel-rich Central Asian countries lead in the RE segment, whereas hydrocarbon-poor economies have almost no RE facilities in place. This paper seeks to explore such possibilities in Central Asia. Section one reviews the evolution of the energy security concept. Section two examines the regional context for energy cooperation. Section three analyses the economic and energy profiles of Central Asian economies. Section four investigates nations' RE policies and explores the RE potential in each economy. In section five, the common regional and specific national barriers for RE development are discussed in detail. Section five also contains our recommendations about ways to ensure energy security through regional energy cooperation, and characterizes the essential components of comprehensive national policies to enable a fuller utilization of the RE potential existing in Central Asia. Finally, section six presents our conclusions.
Keywords: O13; P28; P33; Q28; 330; Central Asia; energy resources; international cooperation; government policy for renewable energy